Zasebnost in internet - Pivec, Franci (Uporabna informatika (Ljubljana), 2000)
With the appearance of the Internet, privacy, especially information privacy, has been confronted with new forms of threat. The state laws in different countries perceived this phenomenon with diverse levels of intensity, though international conventions regarding this issue play a very important role here (OZN, EU, OECD). An apparent disharmony is seen between the prescribed image and the real life situation, since in many countries neither the country's own regulations, nor the international ones are observed consequently, which is often connected with the policy to control people and organisations. A special case is the protection of information privacy at work, where the workplaces are increasingly equipped with the Internet. Another, even more menacing threat to the information privacy is sending "spam", which is unsolicited email. Undoubtedly, the information technology in itself is not the culprit in jeopardising the privacy; it is the people using it that are to blame.
Keywords: informacijska tehnologija; internet; osebni podatki; pravna ureditev; varovanje; zakonodaja; zasebnost